2019
DOI: 10.1021/acsami.9b16404
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance of Nonfullerene Organic Solar Cells over 13% by Employing Silver Nanowires-Doped PEDOT:PSS Composite Interface

Abstract: Ag nanowires (NWs)/PEDOT:PSS composite was prepared by a facile solution-processing method and employed as anode interface in nonfullerene organic solar cells (OSCs). In the presence of a Ag NWs (5%, v/v%)/PEDOT:PSS interfacial layer, a high-power conversion efficiency up to 13.53% was achieved based on a PBDB-T-2Cl:IT-4F photoactive layer system, much higher than the efficiency of the controlled counterpart device with pristine PEDOT:PSS as anode modifier. Simultaneous enhancements in short-circuit current an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Various conductive materials, such as graphene, [ 20,21 ] conductive polymers, [ 22,23 ] metal grids, [ 24–26 ] and metal nanowires, [ 2,27,28 ] have been reported for preparing high‐performance FTEs. Among these, silver nanowire (AgNW) electrodes are recognized as the most promising owing to their high light transmittance, low sheet resistance, good processability, and excellent flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Various conductive materials, such as graphene, [ 20,21 ] conductive polymers, [ 22,23 ] metal grids, [ 24–26 ] and metal nanowires, [ 2,27,28 ] have been reported for preparing high‐performance FTEs. Among these, silver nanowire (AgNW) electrodes are recognized as the most promising owing to their high light transmittance, low sheet resistance, good processability, and excellent flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Although AgNWs demonstrate many outstanding properties, to date, considerable efforts have mostly been devoted to the incorporation as transparent bottom electrodes to replace indium tin oxide (ITO) for highly efficient OPVs with reflective top electrode. [ 24–29 ] It was found that postprocessing treatments, such as high‐temperature thermal annealing (200 °C for 10–30 min), mechanical pressing, and so on, are usually required to reduce the contact resistance between the nanowires and hence achieve a desired electrical conductivity. Obviously, these treatments limit AgNWs in applications where it is used as the top electrode, especially for the devices that contain heat‐sensitive semiconducting materials, where postprocessing temperature can critically and negatively impact a carefully created and optimized morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The J sc and V oc parameters depend on light intensity (P), and the incorporation of these two OCILs materials was also investigated in comparison with the bare ZnO/ITO cathode. Normally, J sc and P follow the relationship of J sc ∝ P α . Here, the α values based on PMI‐TPP and PMI‐TMOPP OCIL are 0.980 and 0.974, respectively, which are slightly higher than the bare ZnO/ITO cathode device's value of 0.973 (Figure S7b, Supporting Information).…”
Section: Resultsmentioning
confidence: 86%